Genomic and epigenetic insights into the molecular bases of heterosis - Chen, Z. J.
Heterosis, also known as hybrid vigour, is widespread in plants and animals, but the molecular bases for this phenomenon remain elusive. Recent studies in hybrids and allopolyploids using transcriptomic, proteomic, metabolomic, epigenomic and systems biology approaches have provided new insights. Emerging genomic and epigenetic perspectives suggest that heterosis arises from allelic interactions between parental genomes, leading to altered programming of genes that promote the growth, stress tolerance and fitness of hybrids. For example, epigenetic modifications of key regulatory genes in hybrids and allopolyploids can alter complex regulatory networks of physiology and metabolism, thus modulating biomass and leading to heterosis. The conceptual advances could help to improve plant and animal productivity through the manipulation of heterosis.